Cost of Production Calculation of Tofu SMEs Factory in Tebing Linggahara Village - Dinda Karasinta Hasibuan; Yudi Prayoga; Mulya Rafika (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This activity is motivated by data showing that the results obtained when observing small tofu factories are still very low. In response to this, the researchers conducted the research aiming to increase the productivity of the tofu factory SMEs in the village of Clifflinggahara by providing knowledge on how to calculate the cost of production (HPP). The objectives to be achieved in this service include (1) knowing the implementation of the experimental method at the tofu factory SMEs in the Cliff Linggahara Village, (2) knowing the increase in productivity results at the Tofu Factory in the Cliff Linggahara Village (3) being able to apply how to calculate the cost of goods sold (HPP) to make it easier to set the selling price of the product. This service is carried out in the village of Tebig Linggahara. This study measured all production results carried out by the tofu factory UMKM in the village of Cliff Linggahara. From the results of the study it showed an increase on certain days. From the research conducted, the method of trading MSMEs in the village of Clifflinggahara was quite good and resulted in a fairly stable economic increase.